Implementasi Pembelajaran Berbasis ICT Sebagai Upaya Perguruan Tinggi Menghadapi Era Smart Society 5.0 - Muhammad Taufiqurrahman (PROGRESSA: Journal of Islamic Religious Instruction, 2022)
This research is the result of a literature review from various reference sources such as books, reports, laws and regulations, and scientific journals that are relevant to how the implementation of ICT-based learning as an effort by higher education to face the Smart Society 5.0 Era. Regretting the results of the study of researchers inthe nature of the Smart Society Era 5.0 the learning process by applying ICT must be in line with the capabilities of the 21st century which includes three aspects including learning and innovation skills, life and career skills, and information media and technology skills. In addition, a learning model is also needed that supports the implementation of learning in the Smart Society 5.0 Era which focuses on the theory of learning socio constructivism where educators act as moderators and facilitators who help students find their own knowledge in the learning process. In its implementation, there are three main components in the application of ICT in the learning process in the Smart Society Era 5.0 which include ICT as a learning medium, ICT as a learning tool and ICT as a learning resource.